Conceptualizing person undergoing rehabilitation care in the light of Axel Honneth’s theory of recognition - Steffen, Pâmela Leites de Souza; Antunes, Lucas; Acordi, Indiana; Vargas, Mara Ambrosina de Oliveira; Santos, Evangelia Kotzias Atherino dos; Schoeller, Soraia Dornelles (Revista de Enfermagem da UFPI, 2024)
Objective: To reflect on the concept of person, in the context of rehabilitation, in the light of Axel Honneth’s Theory of Recognition. Methods: Theoretical-philosophical essay. Results: The concepts of person, patient, user or client have given rise to central debates in health care models, especially in the area of rehabilitation. In this context, the concept of person stands out, from an anthropological and theological perspective to the inclusion of the complexity of social interactions in this meaning. Axel Honneth adds to this view by reflecting on the individuation of the being through the foundation of recognition, sustained by the need for self-confidence, self-respect and self-esteem, making it possible to draw up a collaborative care plan that strives for the good life of the person undergoing rehabilitation. Conclusion: We can conclude that conceiving of care centered on people with disabilities is much more coherent nowadays than perpetuating other debatable expressions in terms of health. Regardless of the term to be used, recognizing all the dimensions inherent in the concept of person is fundamental in terms of establishing the integral dialogical relationship that is intended between health professionals and the person-patient-user-client undergoing rehabilitation.